Recent issues of elderly intergenerational instructional strategies: a scoping review - Ali, Muhammad Asri Mohd; Ahmad, Nahdatul Akma; Ariff, Mohamed Imran Mohamed; Alias, Nursyahidah; Baharum, Zirawani; Shahdan, Tengku Shahrom Tengku (Intelektual Pustaka Media Utama, 2024)
This scoping review investigates instructional strategies implemented in recent studies to enhance the digital application usage experience for the elderly, addressing emerging issues in the context of a rapidly aging global population. With the World Health Organization predicting a significant increase in the proportion of individuals aged 60 years and above by 2030, the imperative for digital literacy among the elderly becomes crucial. The review, drawing from 14 eligible articles sourced from Web of Science and Scopus, categorizes findings into two main themes: i) intergenerational strategies of instruction and ii) contemporary issues associated with intergenerational approaches. By exploring these dimensions, the paper provides valuable insights for researchers seeking to understand and tackle current challenges in instructing the elderly on digital applications, contributing to the ongoing discourse on improving the quality of life for the aging population through digital technology.